Religious Authorities in Pedagogy. Metatheoretical Remarks - Magier, Piotr (Paedagogia Christiana, 2016)
The subject of the article is the functions, which in pedagogy are attributed to categories, statements and concepts of the people who are considered to be religious authorities. Many a time in this field of study, the used notions and thesis are formulated by people who are not scientists (e.g. by people who represent a particular religion or creed) in order to introduce justification or assessment of the particular postulates. The widespread use of the argument “from authority” raises questions about the need, legitimacy as well as the scope of this measure. The article is metatopical and analytical in nature. It does not aim at constructing and calling for a model of the analysed relation. It is about formulating fundamental remarks describing theoretical functions, which are attributed to the statements of particular people who are considered to be religious authorities. Additionally, the notes formulated are apprising in nature, which emphasises the problem of the legitimacy of using arguments “from authority” in pedagogy.